2011
DOI: 10.1002/jmri.22614
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a 32‐channel with a 12‐channel head coil: Are there relevant improvements for functional imaging?

Abstract: Purpose: To evaluate the suitability of a 12-or 32-channel head coil and of a prescan normalization filter for functional magnetic resonance imaging (fMRI) studies at different brain regions.Materials and Methods: fMRI was obtained from 36 volunteers executing a visually instructed motor paradigm using a 12-channel head matrix coil and a 32-channel phased-array head coil with and without prescan normalization filtering at 3 T. The time-course signal-to-noise ratio (tSNR) and the magnitude of functional activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 25 publications
2
37
1
Order By: Relevance
“…Nevertheless, choice of coil ultimately did not influence SNR in terms of statistical significance, most likely secondary to the marginal increases and, in some instances, decreases in SNR observed within the caudate and the pons with the 32-channel coil. This phenomenon of decreased central SNR has been observed previously 14,16 and was further confirmed in this study by comparison of peripheral to central SNR ratios (ie, Ratio p j c ) between the coils. This ratio was statistically significantly greater with the 32-channel relative to the 12-channel coil.…”
Section: Figuresupporting
confidence: 76%
See 2 more Smart Citations
“…Nevertheless, choice of coil ultimately did not influence SNR in terms of statistical significance, most likely secondary to the marginal increases and, in some instances, decreases in SNR observed within the caudate and the pons with the 32-channel coil. This phenomenon of decreased central SNR has been observed previously 14,16 and was further confirmed in this study by comparison of peripheral to central SNR ratios (ie, Ratio p j c ) between the coils. This ratio was statistically significantly greater with the 32-channel relative to the 12-channel coil.…”
Section: Figuresupporting
confidence: 76%
“…Seventeen consecutive patients at a Gamma Knife facility (mean [SD] patient age, 64 [14] years) with known brain parenchymal metastatic disease or metastatic disease seen on standard noncontrast MRI scans were recruited prospectively from December 2009 to May 2011. Informed consent was obtained in this institutional review boardYapproved study.…”
Section: Methods and Materials Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the anatomic MTL ROI the statistical threshold for the OI event-related analysis was set to voxel level z ϭ 1.645 and P Ͻ 0.05, uncorrected for multiple comparisons, with a minimum of 9 continuous voxels. A more liberal statistical analysis was used in the OI analysis because of the lower number of observations in the event-related analysis, and due to the expected lower BOLD signal from the MTL due to susceptibility (Ojemann et al 1997(Ojemann et al , 2010) and coil effects (Kaza et al 2011). Moreover, entorhinal BOLD activity in response to odor stimulation has been shown to be substantially smaller than in piriform cortex and amygdala (Tabert et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the within-subject whole brain group level analysis of OI, entorhinal cortex activity was restricted to a small region and had a low z value, whereas many voxels were active with high max parameter estimate values in the anatomic entorhinal ROI. This discrepancy probably stems from a combination of MR technical (Kaza et al 2011;Ojemann 1997Ojemann , 2010 issues combined with local anatomic-physiologic characteristics of odor processing in the entorhinal cortex. In rats entorhinal neurons display odor selectivity (Young et al 1997), and thus both inter-and intraindividual activity to the identified odors may differ, thus contributing to a limited area of activation in the third level group analysis, although activity for each individual was high, as shown in the functional and anatomic entorhinal ROI analyses.…”
Section: Discussionmentioning
confidence: 99%